An investigation of the concurrent and longitudinal associations between narrative coherence and mental health mediated by social support. Issue 4 (5th January 2022) - Vanaken, Lauranne; Bijttebier, Patricia; Fivush, Robyn; Hermans, Dirk
The coherence of autobiographical narratives is thought to be reflective of individuals' psychological adjustment. However, results are not always replicable, the longitudinal nature of the relation has remained largely unaddressed, and there is limited research on mechanisms that may explain the relation between coherence and mental health. Therefore, in a large longitudinal study, we investigated the concurrent and prospective associations of narrative coherence with mental health, as well as mediational effects of perceived social support. Concurrently, correlations showed that total narrative coherence was associated with higher psychological well-being, fewer symptoms of depression and anxiety, and fewer negative social interactions. Cross-sectional regressions showed that total narrative coherence was predictive for better psychological well-being and fewer symptoms of depression and anxiety, and that chronological coherence predicted depressive symptomatology. These relations were all mediated by perceived negative social interactions. Prospectively, over a 5-month time interval, higher coherence of positive narratives predicted relative decreases in depressive and anxious symptoms. These relations were also mediated by the amount of perceived negative social interactions. Individuals who were more coherent about their past positive life events experienced a relative decrease in depressive and anxious symptoms over a 5-month time interval because they experienced fewer negative interactions with their social network over time.